Why the EU Market Stability Reserve deters long-term low-carbon investments - Grischa Perino; Maximilian Willner (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2017)
Postponing the issue date of allowances in a cap-and-trade scheme as instituted e.g. in the Market Stability Reserve (MSR) of the EU ETS has an impact on abatement technology adoption. Stimulating low-carbon investments is a key objective of the MSR. We show that postponing allowances has an ambiguous effect on investments. By constraining intertemporal arbitrage, it shifts investments towards short-term reductions. Long-term investments are deterred. Reform proposals for Phase IV of the EU ETS are suitable to counteract the negative effects of the MSR on long-term investments but undermine the very idea of the MSR. The effects crucially depend on how firms form expectations about future allowance prices.
Keywords: 330